IMUNOPATOLOGI DAN PERSPEKTIF LABORATORIUM KLINIK SARS - COV - 2 : A REVIEW - Dian Nurmansyah; Aldiana Astuti (Klinikal Sains : Jurnal Analis Kesehatan, 2020)
Severe Acute Respiratory syndrome corona virus 2 ( SARS-Cov-2) is a virus from Nidoviridales family Coronaviridae that causes acute respiratory syndrome in humans. The virus discovered in wuhan, China in mid December 2019 and determined as a global pendemic by WHO The management of the patient becomes crucial in suppressing the mortality rate of patients with positive COVID-19. The actual viral infection is self-limited disease with supportive treatment. Good treatment support requires information and clarity of viral pathogenesis, laboratory results, patient clinical symptoms and in-depth analysis of virus characteristics and the body's immune response to infection